Movement-Evoked Pain Versus Pain at Rest in Postsurgical Clinical Trials and Meta-Analyses: Protocol for a Follow-Up Systematic Review - Camiré, Daenis (JMIR Res Protoc, 2020)
BACKGROUND: Postoperative pain is one of the most prevalent and disabling complications of surgery that is associated with personal suffering, delayed functional recovery, prolonged hospital stay, perioperative complications, and chronic postsurgical pain. Accumulating evidence has pointed to the important distinction between pain at rest (PAR) and movement-evoked pain (MEP) after surgery. In most studies including both measures, MEP has been shown to be substantially more severe than PAR. Furthermore, as MEP is commonly experienced during normal activities (eg, breathing, coughing, and walking), it has a greater adverse functional impact than PAR. In a previous systematic review conducted in 2011, only 39% of reviewed trials included MEP as a trial outcome and 52% failed to identify the pain outcome as either PAR or MEP. Given the recent observations of postsurgical pain trials that continue to neglect the distinction between PAR and MEP, this updated review seeks to evaluate the degree of progress in this area. OBJECTIVE: This updated review will include postsurgical clinical trials and meta-analyses in which the primary outcome was early postoperative pain intensity. The primary outcome for this review is the reporting of MEP (vs PAR) as an outcome measure for each trial and meta-analysis. Secondary outcomes include whether trials and meta-analyses distinguished between PAR and MEP. METHODS: To be consistent with the 2011 review that we are updating, this review will again focus on randomized controlled trials and meta-analyses, from Medical Literature Analysis and Retrieval System Online and EMBASE databases, focusing on pain treatment after thoracotomy, knee arthroplasty, and hysterectomy in humans. Trials and meta-analyses will be characterized as to whether or not they assessed PAR and MEP; whether their pain outcome acknowledged the distinction between PAR and MEP; and, for trials assessing MEP, which pain-evoking maneuver(s) were used. RESULTS: Scoping review and pilot data extraction are under way, and the results are expected by March 2020. CONCLUSIONS: It is our belief that every postsurgical analgesic trial should include MEP as an outcome measure. The previous 2011 review was expected to have an impact on more widespread assessment of MEP in subsequent postoperative pain treatment trials. Thus, the purpose of this follow-up review is to reevaluate the frequency of use of MEP as a trial outcome, compared with PAR, in more recently published postoperative pain trials. TRIAL REGISTRATION: PROSPERO CRD42019125855; https://tinyurl.com/qw9dty8 INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/15309